Do Early Diagnosis and Glucocorticoid Treatment Decrease the Risk of Permanent Visual Loss and Early Relapses in Giant Cell Arteritis: A Prospective Longitudinal Study. Issue 14 (April 2016) - Hocevar, Alojzija; Rotar, Ziga; Jese, Rok; Semrl, Snezna Sodin; Pizem, Joze; Hawlina, Marko; Tomsic, Matija
Abstract : Abstract: To determine the incidence of permanent visual loss (PVL) in giant cell arteritis (GCA) and the GCA relapse rate during glucocorticoid (GC) tapering. This prospective, longitudinal single secondary/tertiary rheumatology centre study was conducted between September 2011 and September 2014 in Slovenia. Predetermined clinical and laboratory tests were performed at 12, 24, 48, 96, and 144 weeks after diagnosis. Sixty-eight GCA patients (72.1% female), with a median (IQR) age of 73.2 (67.3–76.1) years and a symptom duration before the diagnosis of a median (IQR) 30 (14–70) days were included. Thirty-nine of 68 patients had symptoms for less than 31 days (14 (10–28) days–early GCA) and 29/68 for 31 days or longer (90 (60–120) days–late GCA). Four (5.9%) patients presented with PVL (1 early GCA). The median (IQR) follow-up was (IQR) 104 (53–126) weeks. GCA relapsed in 17/39 (43.6%) and 14/29 (48.3%) in early and late GCA, respectively. The median (IQR) time to the first relapse was 24.8 (13.6–46.5) weeks (early GCA 14 (13–34) weeks; late GCA 25 (22–48) weeks, P = 0.117), at the methyl-prednisolone dose of 6.0 (4.0–12.0) mg. The patients who relapsed had significantly higher levels of inflammation parameters at the baseline (including ESR, CRP, serum amyloid A, haptoglobin, and fibrinogen). An early GCA diagnosis and prompt GC treatment decreased the PVL rate in comparison to historic controls, but seem to have no impact on the frequency of relapses, which are predicted by the high baseline levels of the biomarkers of inflammation.